Garbhagriha of the main Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
The dvarashakha or main architrave of the garbhagriha (sanctum sanctorum) of the Suswani Mata Temple. This profusely carved architrave is made up of two shakhas (divisions on its vertical sides). The main shakha has a row of female figures on vahanas (mounts). Four on each side of the architrave, these female figures are Saptamartrikas (seven mother goddesses namely Brahmani, Maheswari, Kaumari, Vaishnavi, Varahi, Indrani and Chamunda).